Conceptual Post-Street Art in Russia - Polsky, Anton (SAUC - Street Art and Urban Creativity (repository), 2020)
Global street art turned into a neo-pop(ulist) post-street art (inter)muralist movement operating with simple visual messages easily accessible for people via Instagram. Artists’ anti-capitalist pseudo-critical statements—what I call ‘protest for sale’— circulating in social media are easily co-opted by creative city discourse, the capitalist neoliberal system, discipline society, and the art market. Artists’ voices from peripheral scenes and regions dealing with local contexts, languages, and communities, and those who work in a more nuanced and sophisticated way are overshadowed by street art celebrities and their domesticated rebel aesthetics. Taking as an example Russian conceptual and dialogical post-street art I want to show other perspectives on the development of street art.